Історик і шевченкознавець М.Ткаченко: призабутий ініціатор проекту багатотомної "Історії міст і сіл Української РСР" - Черняхівська, О. (Український історичний журнал, 2018)
Розглядаються певні аспекти біографії доктора історичних наук М.Ткаченка,
фахівця з історичної географії, історіографа й шевченкознавця, вихованця Науково-дослідної кафедри історії України ВУАН, що дають уявлення про його творчий внесок у справу системного вивчення минулого населених пунктів.
Базуючись як на опублікованих джерелах, так і на архівному матеріалі, позначено етапи фахового зростання М.Ткаченка. Реалії доби тоталітаризму відбилися й на його кар’єрі: безпідставні арешти та ув’язнення як «контрреволюціонера», звільнення з системи ВУАН як «грушев’янця», ліквідація очолюваної
ним Археографічної комісії. У повоєнний період упереджене ставлення з боку
директорів Інституту історії АН УРСР М.Петровського та О.Касименка унеможливило проведення М.Ткаченком наукової діяльності у цій установі. Численні праці дослідника, перші з яких було опубліковано ще у середині 1920-х рр.,
свідчать про широке коло фахових інтересів, передусім у царинах історичної
реґіоналістики та містознавства. Робиться висновок, що М.Ткаченко своїми
працями, ідеями, які висував, стояв у витоків створення багатотомного видання з історії міст і сіл Української РСР. Але незважаючи на солідні напрацювання, знання джерельної бази, численні письмові звернення і пропозиції до
інстанцій, відповідальних за розробку концепції й, у подальшому, створення 26-томної «Історії міст і сіл Української РСР», намагання М.Ткаченка безпосередньо повноцінно реалізуватися у цьому проекті так і не було почуто та сприйнято. The paper considers definite aspects of M.Tkachenko’s biography. He was а Doctor
of History sciences, expert in historical geography, historiographer and Shevchenkologist,
a graduate student of the scientific Сhair of History of Ukraine of the
All-Ukrainian Academy of Sciences. This work gives an idea of Tkachenko’s contribution
to the systematic study of the history of the Ukrainian localities. The author,
based on the published sources and archival material, highlights stages of the researcher’s
professional growth, starting from his study at the History and Philology
faculty of St Volodymyr University in Kyiv resulting in presentation of the diploma
paper under Prof. V.Danylevych’s scientific supervision in 1916. Afterwards he, being
a teacher, worked for the above mentioned Academy History & Geography and Archaeography
Commissions, and other Institutes, where obtained the Candidate’s and
Doctor’s of History Sciences degrees in 1942 and 1964 respectively. The realities of
the Stalinism epoch adversely affected M.Tkachenko’s career. He survived unfounded
arrest and imprisonment as a “counterrevolutionary” in 1928 and dismissal from the
Academy of Sciences as M.Hrushevs’kyi’s student in 1933. The Academy Archaeography
Commission headed by him was abolished in 1934. The bias of the Institute of
History of Academy of Sciences of the Ukr.SSR Directors M.Petrovskyi and O.Kasymenko
against him resulted in M.Tkachenko’s activity for other academic institutions
in the post-war time. A number of M.Tkachenko’s works published since the middle
of 1920‑ies, testify to the wide range of his interests, in the fields of historical regional
science and urban history especially. His professional scientific activity and ideas
that he put forward, suggest his being at the cradle of the creation of the unique
multi-volume edition on the history of the cities and villages of the Ukrainian SSR.
However, despite scientific achievements, perfect knowledge of the source base and
numerous appeals and proposals to the institutions responsible for the development
of the concept and, later, the creation of the unique “The History of Cities and Villages
of the Ukrainian SSR” in 26 volumes, M.Tkachenko’s attempts to be directly involved
in preparing the project didn’t meet with success.